Diverse spontaneous silencing of a transgene among two Nicotiana species - Dalakouras, Athanasios; Moser, Mirko; Boonrod, Kajohn; Krczal, Gabi; Wassenegger, Michael (Planta, 2011)
In plants, transgenes frequently become spontaneously silenced for unknown reasons. Typically, transgene silencing involves the generation of small interfering RNAs (siRNAs) that directly or indirectly target cognate DNA and mRNA sequences for methylation and degradation, respectively. In this report, we compared spontaneous silencing of a transgene in Nicotiana benthamiana and Nicotiana tabacum. In both species, abundant siRNAs were produced. In N. benthamiana, the self-silencing process involved mRNA degradation and dense DNA methylation of the homologous coding region. In N.tabacum, self-silencing occurred without complete mRNA degradation and with low methylation of the cognate coding region. Our data indicated that in plants, siRNA-mediated spontaneous silencing is, in addition to mRNA degradation, based on translational inhibition. Differences in the initiation and establishment of self-silencing together with marked differences in the degree of de novo DNA methylation showed that the mechanistic details of RNA silencing, although largely conserved, may vary also in genetically close plant species.